PENGARUH PENAMBAHAN SERBUK BAN BEKAS TERHADAP PARAMETER MARSHALL PADA ASPAL BETON CAMPURAN PANAS LAPIS AUS AC-WC PERKUATAN STRUKTUR KOLOM DAN BALOK AKIBAT PERUBAHAN LAYOUT RUANGAN DENGAN METODE CFRP (STUDI KASUS : PEMBANGUNAN MASJID AS-SHOHABAT TEMBALANG) - N S, Danang Prastyo; Prawesti, Ratih; Sugiharto, Sugiharto; Sukoyo, Sukoyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2018)
This research was conducted to analyse the alternative which might be done to givesolution for column structure reinforcement and bar in case of building room layoutchange. There were 4 methods which were presented for analysing column structurereinforcement and bar in this research. The dimensions of the removed column were25x40 cm with a length of 350 cm and the reinforced beams were 25x40 cm withspan length of 800 cm. This research also showed the price which was gotten fromvarious methods did as consideration of solution chosen. The analysis wasconducted by using SAP2000 application. This analysis was done by 2 columnremoval without reinforcement which in the fact the structure is not powerful if thereis not any reinforcement by the result of 2 column removal so that for safetyanticipation, it is better if reinforcement is implemented. The first method is themethod with the elimination of 2 columns but without the reinforced structure, afterSAP2000 analysis on the portal, obtained the maximum moment that happened was76,1 KN exceeding the permitted moments of 62 KN so that this will be dangerous tothe strength of the structure, therefore for security anticipation should be donereinforcement. The second method which is the first solution is the method ofJacketing Column & Beam obtained the result that the building was considered safeby enlarging the original beam dimensions 25x40 cm to 35x65 cm and the originalcolumns 25x30 cm to 40x40 cm. It is also supported by the value of the momentsshown not exceeding the maximum allowed moments. The third method is analternative to the second retrofit solution by providing additional structuralelements instead of the existing missing columns, but with this method it willinterfere with the aesthetic value of the building, since the new element beams arevery visible. The last method is the use of CFRP (Carbon Fiber ReinforcedPolymer), this method proved to be the most efficient way to overcome the structuralreinforcement problems at As-Shohabat mosque in terms of processing time, laborcost, and sufficient strength to replace the reinforcement that occurs due to thereduction of the column that supports the block.Kata kunci: strengthening column and beam, strengthening structure, CFRP